Marius Victorinus on the Stigmata of the Apostle Paul (Gal 6:17) - Helleman, Wendy Elgersma (Vox Patrum, 2024)
This discussion of the fourth-century commentary of Marius Victorinus on Paul’s epistle to the Galatians serves as a critical witness to late ancient understanding of Paul’s self-identification with the stigmata of Christ (of Gal 6:17), as the marks of his humiliating death on the cross. Echoing Paul on “being crucified with Christ”, Victorinus exhorted Christians to follow that example in suffering for their faith, warning them that suffering is inevitable. The present textual study uses linguistic, grammatical, rhetorical, and socio-historical analysis, particularly on the key terms, stigmata and mysterium. It concludes that Victorinus associated these terms to give meaning to trauma and suffering for Christians. The term mysterium in Victorinus’ work is closely associated with central aspects of Christ’s life and work, especially his crucifixion and death. While rejecting the “history of religions” school of thought on Christian liturgy borrowing from mystery religions, this study concludes that Victorinus’ use of the term mysterium reflects a move in fourth century Christianity to adapt language of the mysteries for the sacraments; more particularly, baptism is understood as a symbolic reenactment of Christ’s crucifixion, death and resurrection. Such an approach enhances the meaning of suffering in terms of service to Christ, for in baptism Christians share not only in Christ’s death, as suffering “with Christ”, but also in his resurrection, as victory over sin, suffering and death.